4D printing of shape memory polylactic acid (PLA) - Mehrpouya, Mehrshad; Vahabi, Henri; Janbaz, Shahram; Darafsheh, Arash; Mazur, Thomas R.; Ramakrishna, Seeram (Polymer (Guilford), 2021)
Additive manufacturing has attracted much attention in the last decade as a principal growing sector of complex manufacturing. Precise layer-by-layer patterning of materials gives rise to novel designs and fabrication strategies that were previously not possible to realize with conventional techniques. Using suitable materials and organized variation in the printing settings, parts with time-dependent shapes that can be tuned through environmental stimuli can be realized. Given that these parts can either change their shape over time to a pre-programmed three-dimensional shape or revert to an initial design, this process has become referred to as four-dimensional (4D) printing. In this regard, the commonly-used polylactic acid (PLA) polymer has been recognized as a compelling material candidate for 4D printing as it is a biobased polymer with great shape memory behavior that can be employed in the design and manufacturing of a broad range of smart products. In this review, we investigate the material properties and shape memory behavior of PLA polymer in the first section. Then, we discuss the potential of PLA for 4D printing, including the principles underlying the strategy for PLA-based printing of self-folding structures. The resulting materials exhibit response to environmental stimulus as well as temperature, magnetic field, or light. We additionally discuss the impact of geometrical design and printing conditions on the functionality of the final printed products. [Display omitted] •The current state of the art on 4D printing of polylactic acid polymer is achieved.•Properties and shape memory behavior of polylactic acid polymer is thoroughly reviewed and discussed.•Various types of shape-shifting behaviors and mechanisms in the 4D printed structures are presented.•The impact of process parameters on the functionality of the fabricated products is discussed.